Análisis del Acarreo Electoral en el Proceso de Elecciones Seccionales 2014 y su Influencia en los Cantones Quilanga y Paltas - Cuenca Granda, María del Cisne (2016)
Quilanga began his political life as of November 8, 1989, while avocados stands out as one of the oldest courts of the country, since its cantonización date is June 25, 1824. The electorate for the process Quilanga 2014 were 4352 inhabitants, while avocados are 19271 inhabitants. Jurisdictions that in recent elections have been influenced by events like the Electoral undemocratic Hauling in that reason a critical analysis of this event, the degree of involvement of the latter in representative democracy is consolidated cantons. The present work has as general objective, identify the causes and effects of Electoral Hauling in Quilanga and avocados cantons during the 2014 regional elections, in the political, economic and social spheres. Changes in voting address is the crucial stage in the process to choose the right candidate as a representative of the masses, here the justification of this analysis, which not only seeks to meet the objectives but also articulate the link between exercise citizen and political rights, participation and commitment, and especially volunteer building a better welfare. Address changes in the province of Loja in 2014 was of 9663 inhabitants, of which 527 were rejected in the two cantons, mostly as a result of the implementation of audit processes developed by the National Electoral Council action taken when it became apparent that voters did not live in the jurisdiction, and most have not been conducted verification processes in previous elections.The electoral law was susceptible of many modifications from 2009 to 2014, about the requirements and procedures for changes in voting address, in order to regulate, ensure and consolidate representative democracy in the country, however the change of address to influence the outcome becomes a means to power, so that candidates (a) and voters unethical and against the poor control of the National Electoral Council, generates effects disinterest of voters in the process, given that the results are not legitimate legally proclaimed. Well as resources and sources of work it focuses on non-originating people of the area, promoting the migration of its inhabitants by escazas sources of employment. Education in democratic rights of citizens by age, whose main objective is to form and consolidate a critical and participatory elector thought in your jurisdiction. So also it arises as a proposal to form a civil court for residency verification or linking voter to the new electoral jurisdiction.